2022
DOI: 10.1136/postgradmedj-2021-141365
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Predictors of COVID-19 vaccine hesitancy in Germany: a cross-sectional, population-based study

Abstract: Purpose of the studyAchieving high COVID-19 vaccination rates is a key public health challenge. The study aims to investigate factors determining COVID-19 vaccine hesitancy and adherence to prevention measures, in German adults.Study designThis cross-sectional study was conducted in Germany, from 21 February 2021 to 3 April 2021, during the strict lockdown period of the third COVID-19 wave. A total of 2029 adults (75.3% women and median age 38 years) participated in an online survey. Participants completed a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 48 publications
1
72
1
Order By: Relevance
“…Medical considerations such as the vaccine’s novelty and medical preconditions seemed to have an effect on the willingness to get vaccinated [ 11 ]. In addition, other factors outside the range of medical-related concerns contributed to the likelihood of getting vaccinated, including educational degree, adherence to COVID-19-related measures, age, sex, the source of COVID-19-related information, and trust in authorities [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Medical considerations such as the vaccine’s novelty and medical preconditions seemed to have an effect on the willingness to get vaccinated [ 11 ]. In addition, other factors outside the range of medical-related concerns contributed to the likelihood of getting vaccinated, including educational degree, adherence to COVID-19-related measures, age, sex, the source of COVID-19-related information, and trust in authorities [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“… 18 Vaccine resistance (refusal) is defined as those people who will definitely not be willing to get vaccinated; vaccine hesitancy is people who are uncertain whether to become vaccinated. 27 , 28 There are three types of vaccines available in Iraq which were included in the present study. These are Pfizer which is an mRNA subtype vaccine, AstraZeneca is an adenovirus subtype 29 and Sinopharm is an inactivated whole virus subtype.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 patients also exhibited a higher risk of systemic complications that include cardiovascular system (myocardial infarction, myocarditis), cerebrovascular events (hemorrhagic infarctions, encephalopathy), and thromboembolic events. The COVID-19 patients’ often presented with significant co-morbidities that included diabetes, hypertension, obesity, and a previous episode of ischemic heart disease ( Umakanthan and Lawrence, 2022 ). A retrospective study conducted in China, revealed that out of 173 severe COVID-19 patients, the prevalence of hypertension, diabetes mellitus, coronary vascular disease, and cerebrovascular disease was significantly higher than non-severe diseases ( Guan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%